Alterity and Repetition. Phenomenological Interpretation of the Divinity in the Later Heidegger - Kageyama, Yohei (Investigaciones Fenomenológicas, 2021)
The purpose of this paper is phe-nomenological interpretation of the various faces of divinity in the later Heidegger and elucidation of the human comportment corresponding to this divinity. In the first chapter, I will make clear the relation between ontological difference in the sense of the later Heidegger and the primordial dimension of divinity which is called the last god (der letzte Gott) and the sacred (das Heilige). Further, the relation between such divinity and entity as a whole (das Seiende im Ganzen) will be clarified. In the second chapter, I will elucidate the place of the divinities in the manifestation of entity as a whole by considering the role of the godlikes (die Göttlichen) in the fourfold (das Geviert). When the primordial alterity of the last god should be experienced in entity as whole, which leads to the notion of the godlikes, it must confront human subject in totally asymmetrical manner. Such asymmetrical communication can be structurally made explicit by taking the concept of “discourse” in Being and Time into account. Finally, I will consider the character of human comportment called preservation (Bergung) with focusing on its relation to the later Heidegger’s conceptions of divinity. This will shed light on how human beings could properly appreciate the experience of what is beyond our understanding and nevertheless supporting our existence. El objetivo de la ponencia es llevar a cabo una interpretación fenomenológica de las diversas facetas de la divinidad en el Hei-degger tardío y elucidar el comportamiento humano respecto de esta divinidad. En el primer capítulo, se esclarece la relación entre la diferencia ontológica en el sentido que le da el segundo Heidegger y la dimensión primordial de la divinidad, llamada el último dios (der letzte Gott) y lo sagrado (das Heilige). A conti-nuación, se esclarecerá la relación entre la divinidad así concebida y lo ente en totalidad (das Seiende im Ganzen). En el segundo apar-tado, se elucidará el lugar de las divinidades en la manifestación de lo ente en totalidad considerando el papel de los divinos la Cuaternidad (das Geviert). Cuando la alteridad primordial del último dios se experimente en lo ente en totaliadd, lo cual conduce a la noción de los divinos, tiene que enfrentarse al sujeto humano de una forma totalmente asimétrica. Esta comunicación asimétrica puede explicitarse estructuralmente mediante la consideración del concepto del discurso en Ser y tiempo. Final-mente, consideraré el carácter del comportamiento humano denominado la preservación (Bergung), con especial atención a su relación con la noción de lo divino en Heidegger tardío. Esto arrojará luz sobre cómo los seres humanos podrían apreciar de manera adecuada lo que está más allá de nuestra comprensión y sin embargo, sostiene nuestra existencia.